Discrete element modeling and large scale experimental studies of bouldery debris flows - hill, K.M.; bereket, Yohannes; dietrich, William E.; hsu, Leslie (Italian journal of engineering geology and environment, 2011)
Bouldery debris flows exhibit a rich variety of dynamics including complex fluid-like behaviour and spontaneous pattern formation. A predictive model for these flows is elusive. Among the complicating factors for these systems, mixtures of particles tend to segregate into dramatic patterns whose details are sensitive to particle property and interstitial fluids, not fully captured by continuum models. Further, the constitutive behaviour of particulate flows are sensitive to the particle size distributions. In this paper, we investigate the use of Discrete Element Model (DEM) techniques for their effectiveness in reproducing these details in debris flow. Because DEM simulations individual particle trajectories throughout the granular flow, this technique is able to capture segregation effects, associated changes in local particle size distribution, and resultant non-uniformity of constitutive relations. We show that a simple computational model study using DEM simulations of a thin granular flow of spheres reproduces flow behaviour and segregation in an experimental model debris flows. Then, we show how this model can be expanded to include variable particle shape and different interstitial fluids. Ultimately, this technique presents a manner in which sophisticated theoretical models may be built which consider the evolving effects of local particle size distribution on debris flow behaviour.